EVALUASI TINGKAT KEAKURATAN ANTARA MODEL SPRINGATE DENGAN MODEL ALTMAN DALAM MEMPREDIKSI DELISTING PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sunaryo Sunaryo (Bina Nusantara University, 2015)
The primary objectives of this research is to learn whether the Springate model and the Altman model can be used to predict delisting, and which model is more accurate, Springate or Altman for industrial company group. This research used quantitative method with secondary data collected by selected random sampling from industrial company groups listed in IDX and preceding researchers’ scientific articles. This research used logistic regression to test hypothesis simultaneously with F test and t test for testing the partial hypothesis. The results of this research describe that either Springate model or Altman model can be used predict delisting and Altman model more accurate than Springate model to predict delisting. The independent variables that affects delisting are earning before interest and taxes to total assets, earning before taxes to current liabilities, working capital to total assets, earnings before interest and taxes to total assets, market value equity to total liabilities, and sales to total assets. It is recommended to further research that the topic of this research can be continued using others company groups or and model. Investors and creditors who invest funds and give loans will select a company that will not be delisted on the future.